Toga Poni: Manfaat dan Prospek bagi Kelompok Wanita Tani Lebah Sari - I Made Pradana Adiputra; Made Ary Meitriana; Ni Wayan Sukerti (Jurnal Pengabdian Pada Masyarakat, 2021)
TOGA PONI: BENEFITS AND PROSPECTS FOR THE BEEHIVE SARI WOMEN FARMER GROUP. To achieve conditions for people who live healthy and prosperous, especially those who do not have large areas of land, hydroponics as a simple technology in farming is the right choice. This effort is the focus of community service activities in the Lebah Sari Women Farmers Group (KWT), Jembong Hamlet, Ambengan Village. Several activities are needed that can support the KWT program in accordance with conditions in the field that have a positive impact that focuses on the lack of understanding of family medicinal plants (TOGA) and planting procedures / hydroponic system techniques as a new flagship program, knowledge of utilization and processing of TOGA for resilience family health and increase the resilience of the KWT economy. Through socialization, counseling and assistance, efforts to provide an understanding of TOGA, hydroponic systems and the prospects for TOGA processing business are important factors for KWT to choose TOGA as a new agricultural activity that supports KWT and a strategic step in facing the current Covid-19 pandemic situation.